Phylogeny of the superfamily Gelechioidea (Lepidoptera: Obtectomera), with an exploratory application on geometric morphometrics - Wang, Qing‐Yun; Li, Hou‐Hun (Zoologica scripta, 2020)
The superfamily Gelechioidea (Lepidoptera: Obtectomera) has a high species diversity. It consists of more than 18,400 described species and has a global distribution. Among it, large numbers of species were reported to be economically important to people's production and life. However, relationships among families or subfamilies in Gelechioidea have been exceptionally difficult to resolve using morphology or single gene genealogies. Multiple gene genealogies had been used in the molecular phylogenetic studies on Gelechioidea during the past years, but their phylogenetic relationships remain to be controversial mainly due to their limited taxa sampling relative to such high species diversity. In this paper, 89 ingroup species representing 55 genera are sequenced and added to the data downloaded from GenBank, and six species representing four closely related superfamilies are chosen as outgroup. The molecular phylogeny of Gelechioidea is reconstructed based on the concatenated data set composed of one mitochondrial marker (COI) and seven nuclear markers (CAD, EF‐1ɑ, GAPDH, IDH, MDH, RpS5, wingless). The phylogenetic results, taking into consideration of the comparative morphological study, show that the clade of Gelechioidea is strongly supported and separated from other superfamilies, which further proves its monophyly. Five families are newly defined: Autostichidae sensu nov., Depressariidae sensu nov., Peleopodidae sensu nov., Ashinagidae sensu nov. and Epimarptidae sensu nov. Meanwhile, a monophyletic “SSABM” clade considered to be closely related is proposed for the first time, consisting of Stathmopodidae, Scythrididae, Ashinagidae, Blastobasidae and Momphidae. Moreover, geometric morphometric analyses using merged landmark data set from fore and hind wings of 118 representative species are conducted. The phenetic tree shows that the monophyly and phylogenetic relationships correspond with the results of molecular phylogeny largely, which well proves its importance and potential application in both phylogenetic reconstruction and species identification.